Gait impairments on single and dual tasks in cerebral amyloid angiopathy: Neuropsychiatry and behavioral neurology/Assessment/Measurement of neuropsychiatric/Behavioral and psychological symptoms. (7th December 2020) - Sharma, Breni; Gee, Myrlene; Zwiers, Angela; Sekhon, Ramnik; Charlton, Anna; Ismail, Zahinoor; Camicioli, Richard; Smith, Eric E.
Abstract: Background: Cerebral Amyloid Angiopathy (CAA) is a small vessel disease wherein amyloid beta protein is deposited in the vessels of the cerebral cortex and leptomeninges. Little is known about CAA and gait impairment, even though gait is known to be affected by Alzheimer's disease (AD). We hypothesized that gait would be impaired in CAA compared to normal controls (NC), and that more complex mental tasks would elicit further impairments in AD compared to CAA. Method: Participants were NC (n=44), non‐demented CAA (n=31), and mild AD‐dementia (n=16). The ProtoKinetics Walkway was used to capture footfalls over a 6 m walk during a single task (walking only) and two dual tasks of differing complexity (counting backwards by ones [simple task] and naming animals [complex task]). For gait velocity, the dual task cost was calculated as the percent change during dual task compared to preferred pace walking. Analysis of covariance was used to test group differences, controlling for age, sex, and height. Result: CAA participants were older and more likely to be men (Table 1). Gait parameters during preferred pace walk, dual task with counting backwards, and dual task with animal naming are shown in Tables 2‐4. Across all three tasks, both CAA and AD performed poorer than NC on mean Stride Length, Stride Length variability, mean Stride Time, mean Velocity, and mean Cadence. However, mean Stride Width, and Stride Width variability did not differ. There were no differences between CAA and AD (Tables 2‐4). On measures of Velocity, the dual task cost for going from single task to counting backwards (simple dual task) was greater in AD than NC but not in CAA than NC (Table 5). The dual task cost for going from single task to naming animals (complex dual task) was greater in AD than CAA and NC. Conclusion: Gait is impaired in CAA to a similar extent as in AD, however dual task cost was higher for AD possibly because of greater cognitive impairment. Future research should investigate causes of gait impairments in CAA, including the effects of hemorrhagic and ischemic lesions such as white matter hyperintensities.